Building the hemisphere community : lessons from the Summit of the Americas process - Hayes, Margaret Daly (Inter-American Dialogue WashingtonUS, 1996)
Provides a complete summary account of exactly what happened during the process of both preparing for and staffing the Miami Summit and in organizing the immediate follow-up to the Summit's Action Plan.